2023
DOI: 10.20944/preprints202312.0719.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Saw Log Recovery in Birch, Black Alder and Aspen Stands of Hemiboreal Forests in Latvia

Jānis Donis,
Guntars Šņepsts,
Pauls Zeltiņš
et al.

Abstract: In any forest stand, the theoretically modelled output of sawlogs (the most valuable roundwood assortments) will differ from what is actually obtained. The aim of this study was to assess whether it is possible to characterize this difference by site properties or inventory parameters of forest element for birch, black alder and as-pen. The differences in yield of sawlogs varied among soil types, and was increasing with age and average diameter of the forest element. The theoretical model for assortment gradin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Birch (Betula spp.) is the dominant broadleaved tree species in hemiboreal Europe, and qualitative birch wood resources are very important for the timber industry, especially the plywood industry [29]. A recent study based on the Norwegian National Forest Inventory has shown that snow is the most frequent damaging agent in birch stands, especially at an intermediate and mature age [30].…”
Section: Introductionmentioning
confidence: 99%
“…Birch (Betula spp.) is the dominant broadleaved tree species in hemiboreal Europe, and qualitative birch wood resources are very important for the timber industry, especially the plywood industry [29]. A recent study based on the Norwegian National Forest Inventory has shown that snow is the most frequent damaging agent in birch stands, especially at an intermediate and mature age [30].…”
Section: Introductionmentioning
confidence: 99%